Plasma levels of oleoylethanolamide in patients with feeding and eating disorders - Catarina Filipa Costa Ferreira (2022)
Purpose: Oleoylethanolamide (OEA) is a bioactive endogenous ethanolamide fatty acid that reduces food intake and suppresses appetite. Dietary intake of oleic acid (OA) can modulate OEA circulating levels in humans. Feeding and eating disorders (ED) are serious mental illnesses with dramatic changes in patterns of food intake. The present study aims to evaluate plasma levels of OEA in patients with anorexia nervosa restricting subtype (AN), bulimia nervosa (BN), and binge-eating disorder (BE). Methods: An observational cross-sectional study was conducted with 68 women, 48 patients with eating disorders according to DSM-5 criteria, and 20 control women. Plasma levels of OEA (in pmol/ml) were quantified using liquid chromatography and mass spectrometry. Results: The plasma levels of OEA were found to be significantly reduced in BE patients (7.1± 1.1) compared to age-control women (28.2± 2.8). In contrast, AN patients with more than 10 years of disease presented a significant increase in OEA plasma levels (35.7± 4.7). BN patients did not present changes in OEA plasma levels. Conclusion: Since OEA, a fatty acid with an anorectic effect, is considerably reduced in BE patients, supplementation with OEA appears to be an attractive choice for a complementary therapeutic approach in BE.